Pricing European Currency Options: A Comparison of the Modified Black- Scholes Model and a Random Variance Model - Chesney, Marc; Scott, Louis (Journal of Financial and Quantitative Analysis, 1989)
Marc Chesney, Louis Scott, Pricing European Currency Options: A Comparison of the Modified Black- Scholes Model and a Random Variance Model, The Journal of Financial and Quantitative Analysis, Vol. 24, No. 3 (Sep., 1989), pp. 267-284